2003
DOI: 10.1890/0012-9615(2003)073[0377:rataip]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Relationships at the Aboveground–belowground Interface: Plants, Soil Biota, and Soil Processes

Abstract: Interactions at the aboveground-belowground interface provide important feedbacks that regulate ecosystem processes. Organisms within soil food webs are involved in processes of decomposition and nutrient mineralization, and their abundance and activity have been linked to plant ecophysiological traits such as species identity and the quality and quantity of plant tissue. We tested aboveground-belowground diversity relationships in a naturally developed plant community of native tallgrass prairie by taking soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
166
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(184 citation statements)
references
References 57 publications
(89 reference statements)
16
166
1
1
Order By: Relevance
“…Infilling of spruce and/or shrubs will change ecosystem nutrient status, snowfall retention, and hydrology (Sturm et al, 2001). Such shifts will likely alter both above-and below-ground biodiversity (Kennedy et al, 2002;Porazinska et al, 2003;Heemsbergen et al, 2004). In addition, the expansion of white spruce into tundra will alter fire frequency and distribution so fire suppression may become an important policy issue in natural resource planning (Flannigan and Van Wagner, 1991).…”
Section: Treeline Advance Into Arctic Tundramentioning
confidence: 99%
“…Infilling of spruce and/or shrubs will change ecosystem nutrient status, snowfall retention, and hydrology (Sturm et al, 2001). Such shifts will likely alter both above-and below-ground biodiversity (Kennedy et al, 2002;Porazinska et al, 2003;Heemsbergen et al, 2004). In addition, the expansion of white spruce into tundra will alter fire frequency and distribution so fire suppression may become an important policy issue in natural resource planning (Flannigan and Van Wagner, 1991).…”
Section: Treeline Advance Into Arctic Tundramentioning
confidence: 99%
“…In an extensive experiment carried out under field conditions, Porazinska et al (2003) tested aboveground-belowground diversity relationships in a naturally developed tallgrass prairie ecosystem by comparing soil biota and soil processes occurring in homogeneous and heterogeneous C3-and C4 plant combinations. Some bacterial and nematode groups were affected by plant characteristics specific to a given plant species, but no uniform patterns emerged.…”
Section: Biodiversity In Soils and Impacts On Ecosystem Functionmentioning
confidence: 99%
“…Through resource availability and niche differentiation, increase in plant biomass and species richness favours the accumulation of soil microbial and faunal biomass and abundance that accommodate greater number of species. Such bottom-up relationships among diversity of food-web organisms occur both aboveground and belowground and are reflected along the trophic cascades (Scherber et al, 2010;Eisenhauer et al, 2013; but see Porazinska et al, 2003). Recent studies on natural grassland plants showed that plant species richness is positively correlated with that of several major fungal groups on a local scale (Hiiesalu et al, 2014;Pellissier et al, 2014).…”
Section: Introductionmentioning
confidence: 99%